Pengembangan Media Sistem Kerja Sensor Berbasis Internet of Things (IoT) pada Program Industri 4.0 SMK - Basirung, Muhammad Romario; Wahyudi (Pusat Data dan Teknologi Informasi Kementerian Pendidikan Kebudayaan, Riset dan Teknologi, 2023)
The development of the industrial revolution 4.0 era and the technology has been influencing various sectors, including education in Vocational High Schools. This educational institution needs to improve students' knowledge and skills in the industry so that they have high competitiveness in the era of the industrial revolution 4.0. One of the most important fields of science in the industrial revolution 4.0 is the Internet of Things (IoT). Therefore, this research aims to develop an IoT-based microcontroller trainer media as an essential learning material in SMK that is valid, practical, and effective. The research method used is Research and Development (R&D) with the modification of 2 development models, namely Waterfall and Prototype. The modification results in syntax/development stages suitable for designing and developing learning products, namely IoT-based sensor learning media. This research is conducted in 5 stages, namely 1) Needs Analysis; 2) Design; 3) Feasibility Test; 4) Implementation; and 5) Evaluation and Revision. The result shows that the IoT-based microcontroller trainer media developed has a very high validity in terms of media and material presented. In addition, the implementation of this trainer media also receives positive responses from students who state that the use of this media trainer is very good.